a RAJA ALI HAJI'S POLITICAL THOUGHTS: RAJA ALI HAJI'S POLITICAL THOUGHTS - Dian Dwi OkPutra; Adian Husaini; Didin Saepudin; Ending Bahruddin (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
Raja Ali Haji was a Malay aristocrat of Bugis descent. A scholar, poet as well as the most prominent and respected statesman in the Riau-Lingga Kingdom who centered on Penyengat Island in the late 19th century. This research was arranged by method qualitative through a historical approach that uses data collection instruments literature review (library research). The data in this study were taken from the works of Raja Ali Haji which has a theme focus on political thought. The findings show The ideal political system for the Malay world in the view of Raja Ali Haji is a royal system based on Islamic law (theo-monarchy). His activities as a political practitioner as well the maturity of the intellectual tradition through its interaction with the classical texts of Al-Ghazâli, Al-Mawardi, and other scholars provide an ethical pattern, namely a pattern that gives emphasis on the ethics of power holders. But, at the same time a thought Raja Ali Haji's politics is also included in the legal style category because he puts forward theories that focus on the theory of the legitimacy of the ruler from the point of view of Islamic law.